2004
DOI: 10.1086/424600
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Attenuated Lentivirus‐Induced Protection in Rhesus Macaques by Administration of Depo‐Provera before Intravaginal Challenge with Simian Immunodeficiency Virus mac239

Abstract: In nonhuman primate models of acquired immunodeficiency syndrome, live attenuated lentiviruses provide the most reliable protection from systemic and mucosal challenge with pathogenic simian immunodeficiency virus (SIV). Although live attenuated lentiviruses may never be used in humans because of safety concerns, understanding the nature of the protective immune mechanisms induced by live attenuated vaccines in primate models will be useful for developing other vaccine approaches. Approximately 60% of rhesus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 55 publications
2
61
2
Order By: Relevance
“…In nonhuman primates, DMPA treatment abrogates the generation of protective immunity to experimental HIV vaccines (7) and cellular responses to simian/human immunodeficiency virus (SHIV) infection (25). Therefore, we examined the effects of DMPA treatment on virus-induced APC activation.…”
Section: Dmpa Treatment Impairs Serum Ifn-␣ Responses To Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nonhuman primates, DMPA treatment abrogates the generation of protective immunity to experimental HIV vaccines (7) and cellular responses to simian/human immunodeficiency virus (SHIV) infection (25). Therefore, we examined the effects of DMPA treatment on virus-induced APC activation.…”
Section: Dmpa Treatment Impairs Serum Ifn-␣ Responses To Viral Infectionmentioning
confidence: 99%
“…In nonhuman primates DMPA increases vaginal transmission of SIV (5), and in mice DMPA causes a 100-fold increased susceptibility to vaginal HSV-2 infection (6). DMPA also blocks development of protective antiviral immunity in these models (7). How Pg impairs innate and adaptive antiviral responses is poorly understood (8).…”
mentioning
confidence: 99%
“…A recent study showed that following treatment with medroxyprogesterone acetate, a progesterone formulation, protection from simian immunodeficiency virus was abolished in immunized monkeys (1). The authors concluded that treatment with progesterone decreased the efficacy of a model vaccine.…”
Section: Vol 79 2005 Hormone Effect On Hsv-2 Infection After Immunimentioning
confidence: 99%
“…Sim-ilar results have been seen in monkeys. In a recent study, treatment of rhesus macaques with medroxyprogesterone acetate prior to intravaginal (IVAG) challenge with simian immunodeficiency virus mac239 abolished attenuated vaccine-induced protection (1).…”
mentioning
confidence: 99%
“…Progesterone, an estrogen antagonist, causes the epithelium to thin and therefore increases susceptibility. In addition to the thinning of the mucosa, progestins are reported to be immunosuppressive in macaque AIDS models and may contribute to disease progression or breaking vaccine protection [97,98]. Other factors in the vagina may also play a role, such as vaginal pH and thickening of mucous.…”
Section: Challenge Routes Of Infection For Testing Vaccine Efficacymentioning
confidence: 99%